2012
DOI: 10.1111/j.1365-2206.2012.00883.x
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and adaptive skills in children of international adoption

Abstract: A B S T R AC TThe attachment pattern of a sample of 168 internationally adopted children was explored in this study using the semi-structured Friends and Family Interview. The pattern was analysed in relation to the development of adaptive skills as an expression of the children's resilience.The secure attachment pattern rates were slightly lower and the insecure attachment patterns were considerably higher than those of normative samples from the previous studies. The children from Eastern Europe demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 32 publications
2
20
1
2
Order By: Relevance
“…More recently, Beijersbergen, Juffer, Bakermans-Kranenburg, and van IJzendoorn (2012) verified that 76% adopted adolescents presented an insecure attachment. Escobar and Santelices (2013) compared the attachment of adopted and nonadopted adolescents and showed that there was a predominance of insecure-avoidant attachment in adopted adolescents, which was in agreement with other existing studies (Barcons et al, 2014;Beijersbergen et al, 2012;van den Dries et al, 2009).…”
supporting
confidence: 88%
See 2 more Smart Citations
“…More recently, Beijersbergen, Juffer, Bakermans-Kranenburg, and van IJzendoorn (2012) verified that 76% adopted adolescents presented an insecure attachment. Escobar and Santelices (2013) compared the attachment of adopted and nonadopted adolescents and showed that there was a predominance of insecure-avoidant attachment in adopted adolescents, which was in agreement with other existing studies (Barcons et al, 2014;Beijersbergen et al, 2012;van den Dries et al, 2009).…”
supporting
confidence: 88%
“…Previous to adoption, most adopted adolescents had been institutionalized, and the literature suggests that the experiences of institutionalization and neglect tended to exert influence on the development of the attachment relationship to be established with adoptive parents (Barcons et al, ; van den Dries et al, ). Adoptees were also more likely to develop lower quality attachment relationships when compared to their peers who had never been separated from birth families (Barcons et al, ; Barone & Lionetti, ; Lionetti, ; van den Dries et al, ). This study may suggest an overrating of the results and should be followed up by further research with a more detailed analysis to confirm this possible bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were found in the adopted population in Spain. The majority of adopted children in our country achieves a standardized adaptation level (Barcons et al, 2014;Palacios & S anchez, 1996), but some show higher rates in inattention and hyperactivity symptoms (Ber astegui, 2007;Palacios & S anchez, 1996), more difficulties in adjustment to school (Reinoso & Forns, 2012), and higher insecure attachment patterns (Barcons et al, 2012).…”
mentioning
confidence: 97%
“…Attachment theory has been found to play a role in stress resilience (Barcons et al, 2014;Shibue & Kasai, 2014). Briefly, attachment theory proposes that an infant's desire for proximity to his or her attachment figure, or caregiver, is a biological drive, rather than a learned behavior (Bowlby, 1969).…”
Section: Relationship Between Hrv and Factors Of Psychological Resilimentioning
confidence: 99%